Designing an E-Learning System at SD Muhammadiyah 2 Kupang Based on Web - Tri Ana Setyarini; Gregorius Rindu Iriane; Jimi Asmara (Institute of Computer Science (IOCS), 2022)
SD Muhammadiyah 2 Kupang is one of the institutions engaged in the world of education, especially at the elementary school level. Learning at Muhammadiyah 2 Kupang Elementary School using conventional or face-to-face methods became disrupted due to the Covid-19 pandemic that hit in Indonesia, learning at Muhammadiyah 2 Kupang Elementary School which was originally conventional, namely teachers and students doing the teaching and learning process directly in the classroom was forced to carry out online learning activities, namely students learning and teaching teachers must keep running even though students are at home. As a result, teachers have to do online learning using online media. This results in many teachers having difficulty in using online media to deliver material and assign assignments to students. Instead, the students have difficulty in checking the materials and tasks given by the teacher. The data collection techniques used in this study are interviews, library studies, observations and questionnaires, the creation of this application using Adobe Dreamweaver and MySQL databases. The results achieved in the creation of this e-learning design will facilitate the learning and teaching process between teachers and students in online learning. It is hoped that this e-learning design can help improve teaching and learning activities at Muhammadiyah 2 Kupang Elementary School.